Baseline factors affecting diabetic macular oedema resolution after intravitreal dexamethasone implant treatment: post hoc analysis of the MEAD study - Carolina C. S. Valentim; Hongxin Lai; Miller J. Ogidigben; Rishi P. Singh; Katherine E. Talcott (BMC Ophthalmology)
Abstract Background Considering evidence that some baseline clinical parameters correlate with diabetic macular oedema (DME) response to intravitreal anti-VEGF treatment and prognosis, investigation of baseline characteristics that could predict treatment response to dexamethasone intravitreal implant (DEX) and facilitate treatment selection was warranted. This study evaluated the relationship between baseline characteristics and time to first DME resolution in patients treated with DEX. Methods This post hoc analysis of the MEAD study (which consisted of 2 randomised, multicentre, masked, sham-controlled, phase 3 clinical trials identical in design) included 351 eyes treated with DEX 0.7 mg and 350 with sham over 3 years, with retreatment possible every ≥ 6 months if eligibility criteria were met. The effect of baseline characteristics on the time to first DME resolution (defined as central retinal/subfield thickness [CRT] < 250 μm) was evaluated with univariate and multivariate models, and further assessed with Kaplan-Meier method. Results The median (95% CI) time to first DME resolution was 9.0 (8.5–9.3) months for the DEX group. The hazard ratio for DME resolution (DEX versus sham) was 2.09 (P < 0.0001). Higher CRT was associated with longer time to DME resolution. Conclusions Treatment with DEX shortened the time to DME resolution compared with sham. Higher CRT was associated with longer time to DME resolution. These findings may influence therapeutic decisions. Trial registration clinicaltrials.gov NCT00168337 and NCT00168389.